(untitled) (Jurnal Teknologi (Sciences & Engineering), 2025)
Individuals with autism frequently struggle with emotion expression and emotion regulation. This study examines the relationship between electroencephalogram (EEG) band signal amplitude and mood in individuals with autism spectrum disorder (ASD) and typically developing (TD) individuals. Ten individuals with ASD and ten individuals with TD participated in this study. The participants wore wireless dry EEG sensors (MUSE 2) in order to get the EEG signal. The previously processed signals were classified as delta, beta, theta, delta, and gamma waves. In addition, positive mood, neutral emotion, and negative emotion are categorized in this study. In conclusion, the results of this investigation revealed substantial disparities in EEG signal amplitude between those with ASD and those with TD when experiencing distinct emotions. There are significant differences in 13 out of 20 EEG band signals from 4 electrodes for particular emotions in the ASD group.